2008
DOI: 10.3168/jds.2007-0889
|View full text |Cite
|
Sign up to set email alerts
|

How Does Live Yeast Differ from Sodium Bicarbonate to Stabilize Ruminal pH in High-Yielding Dairy Cows?

Abstract: The objectives of this study were to evaluate the capacity of 2 dietary feed additives, sodium bicarbonate and live yeast Saccharomyces cerevisiae (strain Sc 47), in optimizing ruminal pH in dairy cows and to determine their modes of action. Three early lactating Holstein cows, fitted with ruminal cannulas, were allocated in a 3 x 3 Latin square design. They were given a total mixed ration as control diet (CD) at a daily feeding rate of 28.0 kg of dry matter (DM)/cow supplemented with 150 g/d of sodium bicarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
146
2
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(186 citation statements)
references
References 29 publications
28
146
2
10
Order By: Relevance
“…The increase in acetate concentration in the rumen of goats receiving a diet supplemented with live yeast might result from the increase in the number of cellulolytic bacteria, as the enhanced acetate level was associated with a higher activity of fibrolytic enzymes and with increased disappearance of NDF from hay incubated in sacco in the rumen. Our results are also in agreement with other studies focused on the effect of live yeast on the concentration of acetate in the rumen (Marden et al, 2008;Křížovă et al, 2011). In contrast, Brossard et al (2006) did not observe an increase in the ruminal acetate concentration in sheep.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The increase in acetate concentration in the rumen of goats receiving a diet supplemented with live yeast might result from the increase in the number of cellulolytic bacteria, as the enhanced acetate level was associated with a higher activity of fibrolytic enzymes and with increased disappearance of NDF from hay incubated in sacco in the rumen. Our results are also in agreement with other studies focused on the effect of live yeast on the concentration of acetate in the rumen (Marden et al, 2008;Křížovă et al, 2011). In contrast, Brossard et al (2006) did not observe an increase in the ruminal acetate concentration in sheep.…”
Section: Resultssupporting
confidence: 83%
“…The VFA concentration was significantly higher in goats fed the control diet or ration supplemented with live yeast than in animals receiving the ration enriched with yeast metabolites. Doležal et al (2005) and Marden et al (2008) reported that live Saccharomyces cerevisiae increased total VFA in the rumen of cows. In contrast to the cited authors, Brossard et al (2006) and Galip (2006) showed that live yeast cells did not modify total VFA, but according to Doreau and Jouany (1998), the effect of live yeast on total VFA in rumen of dairy cows was transient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeasts, in particular different strains or commercial products of Saccharomyces cerevisiae, have been tested on dairy cows with a number of positive effects such as increased dry matter intake (DMI) and milk production (Wohlt et al,1998;Dann et al, 2000); improved diet digestibility (Erasmus et al, 1992;Marden et al, 2008); stabilized rumen pH (Bach et al, 2007); and stimulated rumen bacteria growth (Newbold et al, 1995). However, there are also many studies with no or negative responses to yeast supplementation (Mwenya et al, 2005;Longuski et al, 2009;Chung et al, 2011), probably related to the strong influence of the basal diet, the variation in yeast strains and the different commercial formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies have indicated that supplementation of yeast to the diet may improve feed intake (Williams et al 1991), weight gain (Tripathi and Karim 2011), digestion (Jouany et al 1998), numbers of anaerobic and cellulolytic bacteria (Newbold et al 1995), ruminal pH value (Bach et al 2007) and alter the patterns of SCFA (Marden et al 2008). However, animal responses to yeast supplementation have not been consistent.…”
mentioning
confidence: 99%